PREJUDICE AND DIVERSITY: THROUGH THE ALLEYS OF THE INCLUSIVE SCHOOL.: pelos becos da escola inclusiva (TEL Tempo, Espaço e Linguagem, 2021)
the present seeks to discuss the role of the school in deconstructing negative stereotypes related to non-white cultures and to point out some possible ways to approach the contents listed in law 11.645/08 having as its concepts such as: cultural diversity, culture and cultural identity. Also, think teaching practice under the teacher look that moves by school alleys, place of escape, where they hide prejudices, stereotypes and misdemeanors.Keywords: Law 11.645/08. Afro-Brazilian culture. Teaching practice.